Fiscal Pressure and Air Pollution in Resource-Dependent Cities: Evidence From China - Hui, Changhong; Shen, Fei; Tong, Lu; Zhang, Jingru; Liu, Bei (Frontiers in Environmental Science, 2022)
Under the dual pressure of central environmental performance appraisal and fiscal pressure, local Chinese governments, especially those in resource-dependent cities, struggle with reprioritizing environmental protection over economic growth while staying under budget. However, the empirical impact of such endeavors on pollution control remains underexplored. Based on 2003-2018 panel data on resource-dependent cities in China, this paper adopts a dynamic panel model to explore the effect of local government fiscal pressure on air pollution. The results show that (1) due to the effect of path dependency on existing economic development patterns, resource-dependent cities suffer from a vicious circle where fiscal pressure aggravates air pollution emissions. (2) As shown by the heterogeneity test, air pollution emissions increase significantly as financial pressure becomes severe; the situation also worsens in mature-type resource-dependent cities. (3) The increase in the number of years in the office of top local government leaders exacerbates the negative effect of fiscal pressure on air pollution; in contrast, the increase in age of these officials mitigates the negative effect. (4) The results of the mechanism test show that financial pressure mainly aggravates environmental degradation by hindering industrial structure upgrading and inhibiting urban green innovation.